Trije zgledi neposrečenega prevoda zaradi "lažnih prijateljev" - Derganc, Aleksandra (Linguistica (Ljubljana), 2006)
Some examples of incorrect translation from Slovene to Russian resp. from Russian to Slovene are discussed in the paper. All mistakes are due to "false friends", especially frequent in genetically related languages. An interesting mistake can bi found in a translation from Slovene to Russian. The author used a rare verb razlepotiti in the meaning of 'taking away the beauty'when speaking of what happened to a valley after industrialization. The Russian translator connected the verb razlepotiti because of the structural similarity with the Russian verb ???????????, which means exactly the opposite: to decorate, to adorn. It is suggested in the paper that this mistake wouldn't happen if the translator payed more attention to values prevailing in Slovenia in the period when the book had been written. In the 70ties (and of course later) the idea of industrialization embellishing a valley was inconceivable.
Keywords: homonimi; lažni prijatelji; prevajanje; Russian; ruščina; Slovene; slovenščina; translation